2023
DOI: 10.34133/cbsystems.0034
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Frequency Coupling and Intelligent Neuromodulation

Abstract: Cross-frequency coupling (CFC) reflects (nonlinear) interactions between signals of different frequencies. Evidence from both patient and healthy participant studies suggests that CFC plays an essential role in neuronal computation, interregional interaction, and disease pathophysiology. The present review discusses methodological advances and challenges in the computation of CFC with particular emphasis on potential solutions to spurious coupling, inferring intrinsic rhythms in a targeted frequency band, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 152 publications
0
10
0
Order By: Relevance
“…Neuromodulator approaches based on feedback from PAC modulation have been proposed as tools to quantify motor impairment in patients and to aid in therapy modulation by adjusting stimulation parameters [ 18 , 19 , 20 , 23 ]. This approach proposes the detection of changes in motor symptoms based on PAC increases, which would then lead to adjustments in stimulation, improving the efficacy of this technique [ 23 ]. A phase-targeted stimulation technique has been proposed as a promising method of modulating PAC increases in the motor cortex [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neuromodulator approaches based on feedback from PAC modulation have been proposed as tools to quantify motor impairment in patients and to aid in therapy modulation by adjusting stimulation parameters [ 18 , 19 , 20 , 23 ]. This approach proposes the detection of changes in motor symptoms based on PAC increases, which would then lead to adjustments in stimulation, improving the efficacy of this technique [ 23 ]. A phase-targeted stimulation technique has been proposed as a promising method of modulating PAC increases in the motor cortex [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Promising and attractive applications of a neural interface range from neuroscience research, [1,2] brain-computer interfacing (BCI), [3,4] and body function reconstruction [5,6] to the diagnosis and treatment of neurological disorders. [7][8][9] Substantial efforts have been devoted to developing such platforms to facilitate the recording and modulation of the activity of neural systems, either at the level of individual neurons or across large areas and volumes of the brain. [10][11][12][13][14][15] Non-invasive devices, such as wearable electroencephalogram (EEG) arrays, can measure brain activity at a distance from the neural tissue with little risk, but suffer from signal distortion, low spatial resolution, and background noise due to the attenuating and low-pass filtering effect of the skull and scalp.…”
Section: Introductionmentioning
confidence: 99%
“…Promising and attractive applications of a neural interface range from neuroscience research, [1,2] brain‐computer interfacing (BCI), [3,4] and body function reconstruction [5,6] to the diagnosis and treatment of neurological disorders [7–9] . Substantial efforts have been devoted to developing such platforms to facilitate the recording and modulation of the activity of neural systems, either at the level of individual neurons or across large areas and volumes of the brain [10–15] .…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic oscillatory activity within complex brain structures is believed to reflect both physiological and pathophysiological processes 7 . Recent studies of patients undergoing DBS surgery have revealed how synchronized oscillatory activity across the cortico-basal ganglia circuit can contribute to gait kinematics and motoric impairments in PD [8][9][10][11] . For example, it has been shown that excessive STN activity at beta frequencies (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), which is traditionally thought to be related to both bradykinesia and rigidity, can also precede paroxysmal episodes of freezing of gait (FOG).…”
Section: Introductionmentioning
confidence: 99%